Rapid qualitative and quantitative analyses of anthocyanin composition in berries from the Tibetan Plateau with UPLC-quadruple-Orbitrap MS and their antioxidant activities. Issue 4 (August 2020) - Jia, Qiangqiang; Dong, Qiuxia; Sang, Qingni; Wang, Mingfang; Zhang, Hongyang; Zhou, Yiqun; Li, Yuxi; Xiao, Tingting; Hu, Ping; Zhang, Shoude
Nitraria tangutorum B. (NT), Hippophae rhamnoides L. (HR), Lycium ruthenicum M. (LR), Lycii fructus (LF), Rosa xanthina L. (RX), and Rubuscor chorifolius L. f. (RC) are six berries from Tibetan Plateau. They have been used in traditional folk medicine with a long history, which are rich in anthocyanins. However, detailed study of their anthocyanins remains scarce. Therefore, a method for rapid simultaneous identification and quantification of 12 anthocyanins from berries using UPLC-Quadruple-Orbitrap MS system (UPLC-Q-Orbitrap MS) was established in this work. It was verified with limit of detection (3.86–11.61 µg/L), limit of quantification (3.86–11.61 µg/L), precision (0.95–2.38%), repeatability (0.96–2.08%), stability (0.86–2.31%), mean recovery (95.8–103.1%), recovery range (93.1–107.2%) and RSD less than 5.21%. It was then used in the analysis of anthocyanins in six berries species; 8, 7, 7, 7, 6 and 9 species of anthocyanins have been identified in NT, LF, LR, HR, RC and RX, respectively based on their own retention time and exact mass in positive mode, and for the first time quantified successfully in each berry (31.11 ± 0.42–2978 ± 25.67 μg.g −1 ). Finally, 2, 2-azinobis (3-ethylbenzthiazoline-6-sulphonic acid) (ABTS) radical scavenging activity (0.92 ± 0.12–5.61 ± 0.23 mM TE/100 g), ferric reducing antioxidant power (FRAP) (1.23 ± 0.15–7.42 ± 0.28 mM TE/100 g) and total antioxidant activity (T-AOC) assays were used to evaluate the antioxidant activities of the six berries.